Agency theory and the influence of equity ownership structure on corporate diversification strategies - Denis, David J.; Denis, David J.; Denis, Diane K.; Denis, Diane K.; Sarin, Atulya (Strategic Management Journal, 1999)
We articulate the agency theory view of managerial decision making and its implications for corporate diversification strategies. From agency theory, we generate testable predictions for the relation between equity ownership structure and diversification strategies and review the existing evidence on this relation. On balance, the evidence strongly supports the view that ownership structure influences corporate strategy. Copyright © 1999 John Wiley & Sons, Ltd.